INNV-09. SURGICAL STRATEGIES FOR OLDER PATIENTS WITH GLIOBLASTOMA. (12th November 2021) - Barak, Tanyeri; Hwang, Lee; Chen, Justin; Jin, Lan; Miyagishima, Danielle; Yalcin, Kanat; Ogilvie, Shahiba; Antonios, Joseph; Theriault, Brianna; Huttner, Anita; McGuone, Declan; Lifton, Nathan; et al.
Abstract: OBJECTIVE: Though image-guided surgery with intraoperative magnetic resonance imaging (IoMRI) is associated with higher extent of resection, we aimed to determine the clinical outcome of its use, compared to other less time-consuming intraoperative ultrasound (IoUS), in this patient population. METHODS: Clinical data of 221 consecutive patients aged 70 years or older, who underwent surgical resection for GBM with intraoperative ultrasonography (IoUS) alone or combination of IoMRI + IoUS at Yale New Haven Hospital and Memorial Sloan Kettering Cancer Center were retrospectively reviewed. Variables were analyzed, and comparative analyses were performed, including predictors of overall survival. RESULTS: The addition of IoMRI was not superior to IoUS alone in terms of overall survival (OS) (HR=0.85, 95% CI 0.49-1.47; P= 0.56) or Karnofsky Performance Score (KPS) at 6 weeks postoperatively (OR=0.51, 95% CI 0.22-1.15; P= 0.102). On the contrary, the length of surgery (LOSx) was significantly longer (P< 0.0001) in the IoMRI group. Postoperative complications were significantly less in the IoUS-only group (OR=0.17, 95% CI 0.3-0.46; P=0.002) and in patients who had a preoperative KPS score of 70 or higher (OR=0.092, 95% CI 0.018-0.47; P=0.004). Patients with relatively lower preoperative KPS scores (< 70) showed significant clinical improvement at 6 weeks postoperatively (P=0.0002). Patients with postoperative complications were more likely to have lower KPS scores at 6 weeks postoperatively (OR=0.30, 95% CI 0.10-0.89; P= 0.031), while increased extent of resection was associated with improved KPS scores at 6 weeks postoperatively (OR=2.171, 95% CI 1.22-3.87; P= 0.009). CONCLUSION: Aggressive management with surgical resection should be considered in older patients with GBM, even those with relatively poor KPS scores. The use of IoMRI in this patient population does not appear to yield any survival benefit over IoUS but instead significantly prolongs the length of surgery, increasing the risk for potential postoperative complications.